Patient's perspective: an important issue not to be overlooked in assessing acne severity - SEÇKİN GENÇOSMANOĞLU, DİLEK (JOHN LIBBEY EUROTEXT LTD, 2008)
Acne has significant negative effects on an individual's psychosocial. functions. There is not always a correlation between the severity of acne and its impact on quality of life. Our objective was to evaluate the correlation between quality of life scales and both the physician's and patient's assessments of acne severity and to find out which quality of life scale is more sensitive to changes in acne severity by using generic and acne specific scales. One hundred and twenty acne patients were enrolled. The physician's assessment of acne severity was made by means of Global Acne Grading System. Patients evaluated their acne severity on a 10-point Likert-type scale. Quality of life was measured by the Turkish version of Acne Quality of Life (AQOL) scale and Short Form-36 (SF-36). One hundred and seven patients answered the questions of the AQOL scale completely and were included in the statistical analysis. The AQOL scale did not correlate with the physician's assessment of acne severity whereas there was a correlation between patients' self assessments and AQOL scale. No correlation was found between SF-36 and either the physician's or patients' own assessments. Assessment of acne should not be limited to objective acne severity measures but also include patients' self assessments and acne specific quality of life scales. These measures, which provide a better understanding of patients' perception of severity, are important tools when taking treatment decisions.
Keywords: acne; quality of life; AQOL scale; severity; QUALITY-OF-LIFE; TO-MODERATE ACNE; VULGARIS; DERMATOLOGY; ANXIETY; DISEASE; ISOTRETINOIN; RELIABILITY; DEPRESSION; VALIDITY